Biomonitoring and exposure assessment of people living near or working at an Italian waste incinerator: methodology of the SPoTT study - Bena, Antonella; Orengia, Manuela; Cadum, Ennio; Farina, Elena; Alimonti, Alessandro; Bocca, Beatrice; Chiusolo, Monica; De Felip, Elena; Gandini, Martina; Iamiceli, Anna Laura; Pino, Anna; Procopio, Enrico; et al. (Environmental monitoring and assessment, 2016)
Only few studies on the health effect of waste incinerators were focused on human biomonitoring (HBM). Our aim is to describe a protocol for assessing early variation of selected items in a population group living close to a waste incinerator in Turin, Italy. A cohort of 394 subjects was randomly selected, among residents near the incinerator and residents far from it. To achieve this sample size, 765 subjects were contacted. The cohort was monitored before the start-up of the plant and will be followed up 1 and 3 years after, with measurements of respiratory function, selected blood and urine parameters including 19 metals, 17 congeners of PCDDs/Fs, 12 congeners of DL-PCBs, 30 congeners of NDL-PCBs, 11 OH-PAHs, specific hormones (T3, T4, TSH, cortisol and ACTH) and common health parameters. The same protocol is applied for plant workers and breeders living near the plant. Individual exposure to urban pollution and waste incinerator fallout were assessed through the use of mathematical models. Information on individual habits was assessed using a specific questionnaire. SPoTT is the first Italian study that adopts a longitudinal design of appropriate statistical power to assess health impacts of waste incinerator plants’ emission. The initial results comparing the baseline to the first follow-up are due at the end of 2016.